2018
DOI: 10.2139/ssrn.3125049
|View full text |Cite
|
Sign up to set email alerts
|

Proprietary Data, Competition, and Consumer Effort: An Application to Telematics in Auto Insurance

Abstract: Firms are increasingly able to monitor and collect proprietary data on their customers' behaviors, raising concerns among antitrust authorities that incumbents may use such data to soften competition. Focusing on auto insurance monitoring programs which offer tailored discounts to consumers driving safely, we examine the impact of proprietary data collection on incumbent profits. We find that incumbents' profits initially increase but are eroded by competition from other firms offering similar programs. We fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 14 publications
0
7
0
1
Order By: Relevance
“…Progressive's Snapshot program and Allstate's Drivewise Mobile App are the real-world examples of this kind. Reimers and Shiller (2018) provides many examples of telematics in auto insurance.…”
Section: Information Externalitiesmentioning
confidence: 99%
“…Progressive's Snapshot program and Allstate's Drivewise Mobile App are the real-world examples of this kind. Reimers and Shiller (2018) provides many examples of telematics in auto insurance.…”
Section: Information Externalitiesmentioning
confidence: 99%
“…Michelin follows the same path for truck fleets and charges a fee on its tires for each mile driven (Ramanujam and Tacke 2016, p. 81). Similarly, insurance firms have begun using telematics devices to offer “pay how you drive” auto insurance, a usage-based insurance concept that assesses premiums on the basis of time of usage, distance driven, and driving behavior (Reimers and Shiller 2018).…”
Section: Relating Increments To Pricing Of Servicesmentioning
confidence: 99%
“…Duflo et al (2012) have shown that incentive pay enabled by tech-aided monitoring can raise teachers' attendance rate and consequently student performance. Reimers et al (2018) have found that insurance companies' monitoring technologies reduce driver moral hazard and fatal accidents. Sudhir and Talukdar (2015) have illustrated the role of IT in inducing business transparency by showing more corrupt businesses resist IT adoption more.…”
Section: Literature and Contributionmentioning
confidence: 99%